Evaluation of different media for isolation of Trialeurodes vaporariorum (Homoptera: Aleyrodidae) molds - PEREA-A., ERIKA l.; ROJAS-M., ELEONORA; PINEDA-V., YOLANDA A. (Revista Colombiana de Entomología, 2003)
Greenhouse whiteíly, Trialeurodes vaporariorum (Westwood), causes economic losses of several crops in Garcia Rovira province (Santander). Some research has been conducted in order to study native microorganisms in specific areas and give basic tools for insect pest control. Hence the need to know more about native molds that possibly linked as entomopathogenic motivated this study, in which three different media were evaluated: Complete Agar Medium (CM). 4% Sabouraud Dextrose Yeast Extract Agar (SDAY/4) and Potato Dextrose Agar (PDA).They were used for primary mold isolation from T. vaporariorum with and without the disinfecting of insects using 0.4% sodium hypochlorite. All samples were checked after the second and up to eight days of incubation at room temperature. On CM and SDAY/4 careases of T. vaporariorum showed a similar percentage of mold allowing for a better and major mold isolation, than on PDA. The latter showed a lower percentages of T. vaporariorum mold and difficult mold isolation. The greatest percentage of T. vaporariorum mold was obtained from samples that were not disinfected. Most of the isolated colonies were detected on media after two days of incubation. Seventy percent of isolated colonies (612) were identified. They were: Cladosporium (67%), rusertum (27.45%). Alternaría (2,12%), Mucor (1,63%), Phoma (1,15%) and Penicillium (0,33%).